Dinamika hubungan keterasingan dengan transmisi memori dalam novella Tempête karya J. M. G. Le Clézio: Telaah postmemory - Noer, Nadya Annisa; Udasmoro, Wening; Subiyantoro, Subiyantoro (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
The concept of postmemory, introduced by Hirsch (2012), focuses on the processes through which memories—particularly traumatic memories— of a historical tragedy, “Holocaus”, which is transmitted across generations. Drawing on the elements supporting inter-individual memory transmission, this paper examines the dynamics of human memory within Novel Prize-winning French-Mauritian author J. M. G. Le Clézio's novella entitled “Tempête”. Using a qualitative approach, this study aims to examine the individual forms of memory transmission that are rooted in conditions of isolation, and developed through one trauma site as the memory connector. The presence of semiotics within the story also builds the narration of traumatic memories. It indicates that memory transmission is not necessarily vertical, which is passed from the previous to the next generations. Memory transmission is also not always linear, as there are factors and methods affecting the interpretation of received memory aside from verbally. Thus, the complex relationship between alienation and individual memory transmission processes can directly impact individuals' life projection.